Analysing The Implementation of Content and Language Integrated Learning (CLIL) in Senior High School in Indonesia: A Systematic Literature Review - T. Wisnu Warnia WR; Nafan Tarihoran (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study reviews the implementation of Content and Language Learning (CLIL) in Indonesia senior high school through a systematic review. The review aim to identify research trends, report benefits, and key challenges of CLIL in Indonesia education context. Following the FRISMA guidelines, nine peer-reviewed studies published between 2021 and 2025 were selected from reputable academic databases. The analysis focuses in research design, learning outcomes, and implementation n issues, and it applies the CLIL 4Cs framework—Content, Communication, Cognition, and Culture—as the main analytical lens. The finding indicates that CLIL has appositive impact on student engagement, learning motivation, and better understanding of content and increased confidence in using English in academic context. CLIL also support active learning and encourages higher-order thinking skills. However, the review reveal several challenges that limit effective implementation. These include limited teacher readiness, insufficient English proficiency among teachers and students, lack of collaboration between subject teachers and English teachers, nd difficulties is assessing content and language learning simultaneously. Analysis the 4Cs framework show that Content and Communication are the most emphasized componet in current CLIL practices, while Cognition receives moderate attention and culture is rarely adressed explicitly. The study concludes that although CLIL is feasible and beneficialfor Indonesia senior high schools, its long-term succes depend on continues teacher professiional development, stronger institutional support, and clearer integration within the Merdeka Curriculum. Theis review provide useful insights for educators, researcher, and policemakers to improve bilingual and CLIL-based instruction in Indonesia.